2016
DOI: 10.1186/s12957-016-0999-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of negative estrogen or progesterone receptor expression in patients with luminal B HER2-negative breast cancer

Abstract: BackgroundThe luminal subtype of breast cancer is sensitive to anti-estrogen therapy and shows a better prognosis than that of human epidermal growth factor receptor2 (HER2)-enriched or triple-negative breast cancer. However, the luminal type of breast cancer is heterogeneous and can have aggressive clinical features. We investigated the clinical implications of single hormone receptor negativity in a luminal B HER2-negative group.MethodsWe collected luminal B HER2-negative breast cancer data that were estroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…Our findings were similar to the findings of Bae et al, which indicated that a significant difference in prognosis between single HoR-positive tumors and double HoR-positive tumors, was only observed in HER2-negative tumors, and not in HER2-positive tumors 20 . Several studies also confirmed that single HoR-positive tumors showed worse prognosis than double HoR-positive tumors in the HER2negative group [21][22][23][24] . No significant effect of single HoR-positive tumors in the prognostic assessment of HER2-positive tumors may be related to the results of trastuzumab treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Our findings were similar to the findings of Bae et al, which indicated that a significant difference in prognosis between single HoR-positive tumors and double HoR-positive tumors, was only observed in HER2-negative tumors, and not in HER2-positive tumors 20 . Several studies also confirmed that single HoR-positive tumors showed worse prognosis than double HoR-positive tumors in the HER2negative group [21][22][23][24] . No significant effect of single HoR-positive tumors in the prognostic assessment of HER2-positive tumors may be related to the results of trastuzumab treatment.…”
Section: Discussionmentioning
confidence: 87%
“…This is not consistent with findings from previous studies which did not find significant associations with HER2 positivity and tumour grade or size[ 11 - 14 ]. We hypothesize that this may be due the smaller sample sizes in those studies and the heterogeneity of HER2+ ILC[ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the expression of ER, PR, and/or HER2, breast cancer is commonly classified into four main subtypes: luminal A, luminal B, HER2-enriched, and basal-like subtypes [2831]. Luminal-type breast tumors with ER+ and/or PR+ show a positive response to hormone therapy [32, 33]. A previous study showed that PNPO is induced by estradiol and 4-hydroxytamoxifen in T47D and MCF7 cells (both ER+/PR+), but not in MDA-MB-231 (ER-/PR-) cells [34], implicating that PNPO may correlate with the hormone-related treatment.…”
Section: Discussionmentioning
confidence: 99%